Anticancer Activity of Ni(Ii) and Zn(Ii) Complexes Based on New Unsymmetrical Salophen-Type Ligands: Synthesis, Characterization and Single-Crystal X-Ray Diffraction - Levín-Vásquez, P; Levín-Vásquez, P (Royal Society of Chemistry, 2023)
The discovery of new coordination compounds with anticancer properties is an active field of research due to the severe side effects of platinum-based compounds currently used in chemotherapy. In the search for new agents for the treatment of cancer, unsymmetrical N2O2-tetradentate ligand (H2L1 and H2L2) and their Ni(ii) and Zn(ii) asymmetric complexes (NiII-L1-2 and ZnII-L1-2) have been synthesized and fully characterized. 1H NMR studies revealed that the ligands and complexes were stable in mixtures of DMSO : D2O (9 : 1). Complementary UV-Vis studies confirmed that ZnII derivatives also exhibit high stability in mixtures DMSO : buffer (6 : 4) after 24 h. Single-crystal X-ray diffraction studies confirmed the molecular structures of H2L1, H2L2, NiII-L1, and NiII-L2. At the molecular level, complexes were completely planar without significant distortions of the square-planar geometry according to τ4 parameter. Furthermore, the crystalline structures revealed non-classical intermolecular interactions of the C-H⋯O and the Ni⋯Ni type. The ligands and complexes were screened against the human osteosarcoma (MG-63), human colon cancer (HCT-116), breast cancer (MDA-MB-231) cell lines, and non-cancerous cells (L929). H2L1 and H2L2 ligands not caused cytotoxic effects at a concentration of 100 μM, while NiII-L2, ZnII-L1, and ZnII-L2 complexes induce cytotoxic effects in all cell lines. NiII-L2 was a more active complex against MG-63 (3.9 ± 1.5) and HCT-116 (3.4 ± 1.7) cell lines with IC50 values in the low micromolar range. In addition, this compound was 10-, 5-, and 11-fold more potent than cisplatin in MG-63 (39 ± 1.8), HCT-116 (17.2), and MDA-MB-231 (131 ± 18), respectively. Three complexes exhibited great selectivity for tumoral cells with SI values ranging from 1.6 to 7.4. © 2023 The Royal Society of Chemistry.